2017
DOI: 10.1038/s41598-017-01272-8
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolomics for simultaneously evaluating multiple determinants of primary beef quality in Japanese Black cattle

Abstract: Analytical methodologies to comprehensively evaluate beef quality are increasingly needed to accelerate improvement in both breeding and post-mortem processing. Consumer palatability towards beef is generally attributed to tenderness, flavor, and/or juiciness. These primary qualities are modified by post-mortem aging and the crude content and fatty acid composition of intramuscular fat. In this study, we report a nuclear magnetic resonance (NMR)-based metabolic profiles of Japanese Black cattle to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 50 publications
6
44
0
1
Order By: Relevance
“…Fish freshness has been also examined with NMR (Tan, Huang, Feng, Li, & Cai, 2018), however, only supervised MVSA was used in this study. In another study, 1 H NMR-based metabolomics was used to evaluate parameters associated with the quality of beef (Kodani, Miyakawa, Komatsu, & Tanokura, 2017). Authors analyzed both polar and nonpolar extracts of Japanese Black cattle and found important biomarkers related to the aging process and beef quality indicators.…”
Section: Nmr In Food Authenticationmentioning
confidence: 99%
“…Fish freshness has been also examined with NMR (Tan, Huang, Feng, Li, & Cai, 2018), however, only supervised MVSA was used in this study. In another study, 1 H NMR-based metabolomics was used to evaluate parameters associated with the quality of beef (Kodani, Miyakawa, Komatsu, & Tanokura, 2017). Authors analyzed both polar and nonpolar extracts of Japanese Black cattle and found important biomarkers related to the aging process and beef quality indicators.…”
Section: Nmr In Food Authenticationmentioning
confidence: 99%
“…According to the metabonomics results, lysine, threonine, histidine, alanine, and leucine had a high levels of FAAs among the four groups, which was consistent with previous findings (Careri et al., ). FAAs such as leucine, histidine, tyrosine, valine, and phenylalanine had a bitter taste; both the alanines, threonine, and lysine were known for their sweetness, and aspartate had a umami taste (Dai et al., ; Kodani, Miyakawa, Komatsu, & Tanokura, ). Proper bitterness could be beneficial to the overall flavor of the hams, but excessive bitterness was detrimental to the quality of the hams and was related to excessive hydrolysis of proteins by muscle endogenous enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the bisector of the odd quadrants can be associated with a temperature degradation of meat/or extended storage times. Kodani et al demonstrated that ¹H NMR profiles of water‐soluble metabolites revealed overall metabolic change linearly correlated with beef aging rate and aging duration.…”
Section: Resultsmentioning
confidence: 99%